Auditors' perceptions on obliteration of mandatory annual audit: an empirical study - Salleh, Arfah; Che Rose, Raduan; Samy, Naresh Kumar; Jaafar, Shuhaimi (EuroJournals, 2008)
Fundamentally, an audit is important to several parties to obtain some management and financial information of a company. Indeed the issue of whether or not small companies should be audited has been addressed in many studies in the UK, Australia and some Asian countries such as Hong Kong and Singapore. On contrary, there is dearth of study pertaining to audit exemption of small companies in Malaysia. Thus a research been carried out to examine the perceptions of external auditors and their readiness for exemption of annual audit requirement of small companies in Malaysia, While contributing to the body of knowledge, the findings of this research could help the regulatory bodies to gauge the perceptions of auditors of small companies towards audit exemption. Future research direction been highlighted.